Platelet factor 4 improves survival in a murine model of antibiotic-susceptible and methicillin-resistant Staphylococcus aureus peritonitis - Podolnikova, Nataly P.; Lishko, Valeryi K.; Roberson, Robert; Koh, Zhiqian; Derkach, Dmitry; Richardson, David; Sheller, Michael; Ugarova, Tatiana P. (Frontiers in Cellular and Infection Microbiology, 2023)
The complement receptor CR3, also known as integrin Mac-1 (CD11b/CD18), is one of the major phagocytic receptors on the surface of neutrophils and macrophages. We previously demonstrated that in its protein ligands, Mac-1 binds sequences enriched in basic and hydrophobic residues and strongly disfavors negatively charged sequences. The avoidance by Mac-1 of negatively charged surfaces suggests that the bacterial wall and bacterial capsule possessing net negative electrostatic charge may repel Mac-1 and that the cationic Mac-1 ligands can overcome this evasion by acting as opsonins. Indeed, we previously showed that opsonization of Gram-negative Escherichia coli with several cationic peptides, including PF4 (Platelet Factor 4), strongly augmented phagocytosis by macrophages. Here, we investigated the effect of recombinant PF4 (rPF4) on phagocytosis of Gram-positive Staphylococcus aureus in vitro and examined its impact in a mouse model of S. aureus peritonitis. Characterization of the interaction of rPF4 with nonencapsulated and encapsulated S. aureus showed that rPF4 localizes on the bacterial surface, thus making it available for Mac-1. Furthermore, rPF4 did not have direct bactericidal and bacteriostatic activity and was not toxic to host cells. rPF4 enhanced phagocytosis of S. aureus bioparticles by various primary and cultured Mac-1-expressing leukocytes by several folds. It also increased phagocytosis of live nonencapsulated and encapsulated bacteria. Notably, the augmentation of phagocytosis by rPF4 did not compromise the intracellular killing of S. aureus by macrophages. Using a murine S. aureus peritonitis model, we showed that treatment of infected mice with rPF4 caused a significant increase in the clearance of antibiotic-susceptible S. aureus and its methicillin-resistant (MRSA) variant and markedly improved survival. These findings indicate that rPF4 binding to the bacterial surface circumvents its antiphagocytic properties, improving host defense against antibiotic-susceptible and antibiotic-resistant bacteria.